The role of poverty and community norms in child labor and schooling decisions - Holger Strulik (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2008)
Household poverty is a powerful motive for child labor and working frequently comes at the expense of schooling for children. Accounting for these natural links we investigate whether and when there is an additional role for community norms and how the social evaluation of schooling evolves over time. The proposed model provides an explanation for why equally poor villages or regions display different attitudes towards schooling and why children who are not working are not sent to school either but remain idle instead. The conditions for a successful implementation of a half-day school vs. a full-day school are investigated. An extension of the model explores how an education contingent subsidy paid to the poorest families of a community manages to initiate a bandwagon effect towards an equilibrium where all children are sent to school.
Keywords: I20; I29; J13; O12; 330; School Attendance; Child Labor; Social Norms; Targeted Transfers; Bildungsverhalten; Kinderarbeit; Armut; Soziale Werte; Gemeinschaft; Schulpolitik; Sozialtransfer; Haushaltsökonomik; Konsuminterdependenz; Theorie